Handbook of Signal Processing Systems - Bhattacharyya, Shuvra S.; Deprettere, Ed F.; Leupers, Rainer; Takala, Jarmo (Springer US : Imprint: Springer, 2010)
Handbook of Signal Processing Systems is organized in four parts. The first part motivates representative applications that drive and apply state-of-the art methods for design and implementation of signal processing systems; the second part discusses architectures for implementing these applications; the third part focuses on compilers and simulation tools; and the fourth part describes models of computation and their associated design tools and methodologies. This handbook provides: A comprehensive overview of signal processing systems Standalone, complete reference to signal processing systems A comprehensive index for ease of use An extensive bibliography for further reading This handbook is essential for those involved in R&D in the design, architecture, and implementation of a wide array of signal processing systems. This handbook is also suitable as a first point of entry to the field for undergraduate and post-graduate students in engineering, computer sciences, and system engineering.